‘To TA then BA’: recognising the importance of the ‘told’ life journeys of learners returning to formal education - an investigation into the impact of life experiences on learning - Lane, Susan (2022)
The told life journeys of learners returning to formal education are important to recognise in order to name the learning that occurs in the social contexts of family, community and work and, secondly, to appreciate the compelling connection between this learning and Higher Education (HE). The concept of what is viewed as important lies at the heart of this study which gives voice to the often overlooked mature, part-time student in order to recognise their assets. Despite previous research on older students in HE there is little on their brought assets, gained through past experiences. A biographical approach using semi-structured interviews based on a life-history grid allowed for the voices of the learners to be heard and their stories acknowledged. Findings indicate learning does arise from the everyday and there is a pattern to what is said about the specific intra and interpersonal attitudes and skills accrued. Past experiences are a resource for the adult learner and time spent away from the classroom is not a learning gap. The resulting affective assets are significant to academic study, enhancing and supporting the cognitive. HE needs to see the value of these assets, including motivation, resilience, independence, team work and emotional intelligence, to resurrect the social justice agenda of widening participation and lifelong learning and to seize this academic potential for the benefit of the learners and the academy alike.